Synthesis of (S,5Z,8E,10E)-12-Hydroxyheptadeca-5,8,10-trienoic Acid (12S-HHT) and its Analogues - Tojo, Toshifumi; Wang, Qian; Okuno, Toshiaki; Yokomizo, Takehiko; Kobayashi, Yuichi (Synlett, 2013)
Natural 12S-HHT and its analogues were synthesized for study of structure and activity relationship toward the BLT2 receptor. The Suzuki–Miyaura coupling was used for construction of the 8E,10E-diene moiety of 12S-HHT and analogues of (12R)- and 12-keto-types, whereas Wittig reaction was used for the synthesis of (8Z)- and (8Z,12R)-isomers.
Keywords: asymmetric synthesis; cross-coupling; HHT; Wittig reaction; Suzuki–Miyaura coupling